Burden of the Beast - Bronwyn Fredericks; Abraham Bradfield; Sue McAvoy; James Ward; Shea Spierings; Troy Combo; Agnes Toth-Peter (M/C Journal, 2022)
Introduction Throughout the COVID-19 pandemic, and its fluctuating waves of infections and the emergence of new variants, Indigenous populations in Australia and worldwide have remained at high risk. Indigenous populations are all too familiar with the deadly consequences of introduced disease. Outbreaks such as the H1N1 influenza epidemic in 2009 disproportionately impacted Aboriginal and Torres Strait Islander peoples (Komesaroff et al.; Eades et al.), while past epidemics introduced by colonisers have decimated, and in some cases eradicated entire language groups (Fredericks, Holcombe, and Bradfield). As COVID-19 spreads, and highly contagious variants such as Omicron emerge, preventative measures and vaccinations have never been so important. Vaccination rates in some Indigenous communities, however, remain stubbornly low, with hesitancy coinciding with the spread of misinformation and amplification of conspiracy theories. In some cases, conspiracies have infiltrated Indigenous communities, playing on anxieties derived in part from the impact of colonisation, as well as past and present trauma. The scale of misinformation relating to COVID-19, particularly online, has become a worldwide problem with the World Health Organization terming it an “infodemic” (World Health Organization) and others a “misinfodemic” (Pickles et al.). In this article, we discuss how conspiracies have impacted vaccination rates in some Indigenous communities in Australia. We acknowledge that vaccine hesitancy is not universal amongst all Aboriginal and Torres Strait Islander peoples and that differing responses to public health messaging are informed by diverse socio-historic factors. The most effective strategies towards curbing the spread of misinformation, and hopefully disease, however, arise from community-led and driven initiatives that are informed by evidence-based messaging that empowers Indigenous agency and choice. Methodology Our article draws on a study conducted at the University of Queensland (UQ) which documented and mapped some of the risk and protective measures that influence responses to COVID-19 in urban Brisbane (Fredericks et al. ‘Innovative Research’ and ‘Understanding Health’). Over the course of three workshops, held throughout 2021, stakeholder participants from the Indigenous health sector (both Indigenous and non-Indigenous) – including representation from Aboriginal Controlled Community Health Organisations – shared anecdotal and empirical evidence that amongst other findings demonstrated the impact of circulating misinformation. In this article, we triangulate some of the findings from these workshops with accompanying literature gathered from journal articles, news and social media, and other online sources that have documented accounts relating to conspiracies in Indigenous Australian communities. We argue that successful communications relating to COVID-19 in Aboriginal and Torres Strait Islander communities necessitates that health messaging centralise Indigenous voices and expertise. Conspiracies and Colonialism Settler colonialism is relevant to our discussion concerning the prevalence of conspiracy theories in some Indigenous communities in Australia, as their pervasive nature has shaped a culture of mistrust and scepticism towards dominant hegemonic structures. Colonisation was, and still is, an ongoing process that impacts on Aboriginal and Torres Strait Islander peoples in different regions, in different ways (Wolfe). The prolonged invasion and spread of colonisers throughout the continent resulted in varied, but equally violent, frontier encounters that were informed by the authoritarian structures, policies, and attitudes of the time. Whilst “Indigenous Affairs” – and the policies relating to them – have changed over Australia’s history, responses were/are united through an ethos of “possession” that dehumanises Indigenous peoples and cultures through the proclamation of white sovereignty (Moreton-Robinson). This is demonstrated through state sanctioned practices, such as the removal and institutionalisation of Aboriginal children, now known as the Stolen Generations, or the disproportionate rates of policing and incarceration that have contributed to Indigenous deaths in custody. Missionaries are the by-products of colonisation, and as Noel Pearson has written have complex and conflicting places in some Indigenous peoples‘ lives; being both locations of immense traumas as well as sanctuaries separated from the violence that took place beyond their confines. While missionaries have since transitioned into state-controlled settlements, and then communities and outstations, Christianity and the Christian Church continues to be meaningful for many Indigenous peoples who came from or are kin to those who live in areas formerly controlled and run by religious institutions. As we discuss in the next section, religious dogma and rhetoric has been manipulated and used to target and spread conspiracies about COVID-19 in some Indigenous communities. To better understand conspiracies, however, we argue that we must move beyond the impulse to dismiss them as mere absurdities, but rather unpack the socio-political contexts in which they are constructed, framed, and interpreted (Jane and Fleming). Prasad (13) argues that conspiracies “seem to embody displacement and condensation of not only the past experiences of an individual but also the history of the social group to which s/he/they belong”. Pierre suggests that conspiracies are best understood not through the narratives they propagate, but rather through those they reject. Beliefs in conspiracies therefore can provide a sense membership and belonging among those who rightly or wrongly feel disenfranchised (Douglas et al.). While a sense of disenfranchisement can influence a person’s inclination towards a conspiracy, conspiracists do not always exist on the fringes of society, nor do their theories reflect the nonsensical ramblings of vocal minorities who counter the so-called “rational” views of the mainstream. Within colonial spaces, topics relating to invasion, possession, and dispossession have resulted in conspiratorial silences that veil the ongoing impact of imperialism on Indigenous peoples in Australia and throughout the world (Moreton-Robinson). The failure of settler-nations to confront and address the ongoing violence of colonisation have been described by some as a “conspiracy of silence” (Bottoms and Evans), or a form of hegemonic “amnesia” (Langton). These national silences fuel some Indigenous people’s mistrust in the governing authorities who continuously fail to recognise Indigenous sovereignty. Public health mandates, therefore – when delivered by governments blind to Indigenous cultural protocols – become less about health protection or inoculation per se, but rather serve as touchpoints of conflict that render the unresolved nature of colonisation, visible. In other words, it reflects the question over who has the right and authority to insert their power over Indigenous bodies? Everyday lived experiences with racism, stereotype, intergenerational harm, and maltreatment within the health system can correlate with a person’s receptivity to conspiracy theories (Smith et al.). Indigenous people, and other persons of colour, have long been subjected to maltreatment and/or medical experimentation that has manifested in intergenerational harm and mistrust (Anderson; Pierre). In The Cultivation of Whiteness, Anderson presents a body of work that centralises whiteness within the medical field, outlining how in the twentieth century medicine operated (and still operates) as a “discourse of settlement” through the definition and control of Black bodies (Fredericks). Anderson writes, “the medical construction of white Australia provides another lens through which we may view two hundred years of European settlement” (5). Explanations for vaccine hesitancy amongst Indigenous people – even if they are rooted in conspiracy – cannot be removed from this context of colonial disempowerment. The anti-vax movement – like other discourses and praxes in the public and private sector (Bargallie) – often reflects a racialised colonial discourse. Day and Carlson observe how TikTok influencers and white supremacists in the USA have used language such as “pureblood” in reference to their so-called “supremacy” of having blood untainted by the vaccine (Owen). While messaging such as this often originates abroad, far right groups have strategically manipulated information online so that it may infiltrate Indigenous communities in Australia, preying on pre-existing anxieties. Northern Territory Chief Minister Michael Gunner has directly attributed many of the rumours circulating in Central Australia to foreign intervention (Allam), with similar claims being made in Western Australia and elsewhere (Orr). The Spread of Conspiracy in Indigenous Communities Since the outbreak of COVID-19, numerous conspiracies have emerged attempting to explain the virus through narratives that suggest it is part of an organised initiative to dismantle world order or control global populations. One such conspiracy posits that the virus and the major organisations, individuals, and authorities associated with its prevention are carrying out the work of the devil or the “Beast” (Bohlinge; Letšosa). The spread of misinformation associating vaccines to the “mark of the Beast” has gained momentum in some Aboriginal communities in Australia (Roussos) – particularly in locations that have long histories with Christian missionaries. In some instances, as discussed in the case studies below, individuals have deliberately targeted Indigenous communities and played on anxieties for personal and ideological gain. This is concerning given the already low vaccination rate in communities such as Ali Curung in the Barkley Region, Northern Territory (Roussos), and regions such as the Kimberly and Pilbara where just 10% of the Aboriginal population is vaccinated (Parke and Lynch). Between March and June 2021, emails were sent to the Pastor of Ninga Mia in Western Australia which likened vaccines to the “mark of the Beast” and suggested that it contained an enzyme named after the devil (Richards et al.). These were reportedly sent by Kris Schlyder, the head of the Australian Indigenous Prayer Network in Queensland, who claimed he forwarded the emails after receiving them from a pastor in the United States. Similar examples have occurred in other communities such as Santa Teresa (Roussos). Ninga Mia’s pastor, Geoffrey Stokes, and his wife Dr. Jeffries-Stokes have stated that rumours and awareness of the (false) claims have become so pervasive in their community that vaccine advocacy is met with condemnation by some members of the community who believe the pair have turned their backs on their faith. This suggests that the mere spread of rumour can sow the seed of doubt and exacerbate pre-existing hesitancies. Despite platforms such as Twitter banning the hashtags #MarkOfTheBeastIsTheCovid19Vaccine and #VaccineIsTheMarkOfTheBeast, in attempts to stop the spread of religious misinformation (Dwoskin 2021), they continue to circulate and hinder assurances. In some cases, Indigenous and non-Indigenous service providers have contributed and accelerated the spread of misinformation (Bryne et al.). Community representatives from the Larrakia Nation for example were forced to issue a declaration refuting the views of the Larrakia Sovereign Tribal Council (see Fig. 1) who falsely proclaimed that morgues were in danger of being overrun due to the increasing deaths associated with vaccinations on Groote Eylandt (Bryne et al.). This demonstrates the challenge of how to effectively communicate and expose health messaging from sources that are COVID-19 literate, trusted, and able to counter the spread of misinformation. Fig. 1: Larrakia Nation Facebook post (2021) Involvement of the Australian Defence Force, who assisted in moving residents in remote locations living in overcrowded houses containing upwards of 30 people, has falsely been likened to the Stolen Generations by some (Allam). Historic events and ongoing processes of removing Aboriginal and Torres Strait Islander children; unsolicited involvement of Australia’s Defence Forces during the “National Emergency” of 2007; and other exploits of government intervention in Aboriginal and Torres Strait Islander people’s lives have been manipulated in ways that empowers the divisive agenda of extremist groups. False associations such as these not only impacts vaccine hesitancy but resurface trauma by trivialising past lived experiences and falsifying narratives for a racialised agenda. Katherine community health worker Luke Ellis, whose mother is a member of the Stolen Generations, has stated that any “comparison to stolen generation is spitting on what those poor souls went through in those days” (Allam). There have also been reports of “Blackfishing” in some communities, a process that seeks to manipulate and capitalise on Black culture for economic and/or political gain (Stevens). Blackfishing has targeted remote Indigenous people by falsely associating COVID-19 vaccinations with a “new genocide”. Lorraine Anderson, member of the Kimberley Aboriginal Medical Service, has commented that “unfortunately, because of historical injustice around how the various governments have treated Indigenous people, there is an underlying mistrust of government information. So it’s a minefield for us to work our way around that” (Aboriginal Medical Services Alliance Northern Territory). This poses the question of how to successfully navigate such “minefields” and deliver verified information from trusted sources. Taming the Beast of Misinformation Indigenous peoples have long been aware of the risks of pandemics (Fredericks, Holcombe, and Bradfield) and were quick to implement the measures necessary to ensure the safety of their communities (Fredericks and Bradfield “Indigenous Australians and COVID-19” and “We Don’t Want”). In some locations, testing rates amongst Aboriginal peoples exceeded those of non-Indigenous populations (Wilson-Matenga et al.). Some communities were mobilising and working on messaging before the outbreak was officially declared a pandemic in March 2020 (Stefanoff). Furthermore, Indigenous communities in Victoria embraced vaccination at a rate that exceeded that of non-Indigenous Australians, the success being attributed to transparency, effective communication, and the trust placed in the Victorian Aboriginal Health Services (Syron). In September 2021, the National Aboriginal Community Controlled Health Organisation (NACCHO) organised a meeting with 14 Aboriginal church leaders to discuss the spread of misinformation (Jenkins). Led by NACCHO CEO Pat Turner and Minister for Indigenous Australians Ken Wyatt, the meeting provided an opportunity to discuss strategies to counter misinformation in ways that are culturally appropriate and respectful of communities’ beliefs (Wyatt). Minister Wyatt acknowledged that “uniting faith-based and medical messaging will be key to stamping out the dangerous rhetoric and boost vaccine uptake in Aboriginal and Torres Strait Islander communities” (Coughlan). National Cabinet also met in January 2022, recognising that “everyone was facing difficulties driving Indigenous vaccination rates given misinformation in parts of those [remote] communities" (Stayner). Vicki O’Donnell, the CEO of Kimberley Aboriginal Medical Services, has observed that over her 25-year career, this is the first instance of religious groups being active around the anti-vaccination space. Chief Executive of the Mallee District Aboriginal Services in Victoria Jacki Turfrey has called for more targeted responses to address and dispel each of the myths circulating, indicating that this burden often falls on the shoulders of frontline workers (Bain). Community health organisations and frontline workers have placed considerable time and energy in countering misinformation. In Western Australia, Yamatji Noongar community leader Sharon Wood-Kenney has talked through communities’ concerns in a manner that acknowledges the impact of past government policies such as the Stolen Generations and the understandable mistrust that has come from it, while reiterating the importance and relative low risk of vaccination (Bain). Principle 8 of the Roadmap to Recovery – an independent report devised by a taskforce made up of eight leading Australian universities – refers to the need to counter misinformation through increasing transparency, and in doing so, preventing “information gaps” being filled by conspiracy theories. Frontline Indigenous workers and community leaders who are knowledgeable in health practice, trusted members of their community, and are astute to the diversity of cultural protocols play a vital role in alleviating these gaps (Danchin et al.). Hyland-Wood, Gardner, Leask, and Ecker argue that while trust must be a two-way process between governments and communities, it should always be communicated by credible and trusted sources who have nuanced knowledge specific to particular socio-cultural contexts. Social media networks have provided many Indigenous people with access to information via trusted sources that counter and refute misinformation and/or anxieties associated with dominant heath advice and messaging (Carlson et al.; Fredericks and Bradfield “‘Seeking to Be Heard”; Fredericks et al.). Indigenous communities are taking charge in addressing vaccine hesitancy and the conspiracies often attached to them. COVID-19 has largely highlighted the strengths of Indigenous peoples’ capacity to mitigate risk by implementing the measures necessary for their specific local needs (Wilson-Matenga et al.). As social media is a popular outlet of communication for many Aboriginal and Torres Strait Islander people, in both remote and urban settings (Carlson and Frazer), its ability to disseminate targeted information makes it particularly effective in educating and reassuring communities of the necessity, and relative low risk, of vaccination. Online trends such as posting photos and videos of Indigenous people getting vaccinated, situates the messaging within a local and relational setting. Clear, transparent, and culturally appropriate language and imagery is vital to delivering health messaging. The Ampilatwatja community, for example, translated health messaging into culturally appropriate terms making it not only linguistically comprehensive but placing it within a familiar lived context. Social distancing was translated to ament angkem meaning “separate talking” while arteny, or “sitting down”, was used to explain lockdowns (Stefanoff). In Arnhem Land, the Yolngu word goŋwukundi, meaning a law determining what you can do and where you can go was used to explain “social distancing”. The concept of a virus which is present but invisible was explained via the phrase buwayak warrakan mala describing animals and birds who remain invisible. The importance of framing vaccination as a continuation of ongoing practices of keeping kin and Country healthy – demonstrated through memes such as “My mob said it was okay” (see Fig. 2) – cannot be understated. Fig. 2: uprisingofthepeople (2021) Responses to COVID-19 and the spread of misinformation must be forward-thinking, long-term, and holistic. Interventions and education should be responsive to varying levels of health literacy, as this, paired with disparate socio-economic status and inherent mistrust of mainstream authorities (Lewandowsky and Cook) have correlations to vaccination rates and one’s potential to turn to conspiracies (McCaffery et al.; Pickles et al.). This is exacerbated in “high-impact scenarios” where risk and high probability of a real or perceived threat increases anxieties and creates a “cognitive bias” that informs how such scenarios are understood and responded to (Kovic and Fuchslin). Vaccine hesitancy is best understood and addressed in relation to the interlocking factors that drive anxieties and limit vaccine uptake (Goorie; Fredericks et al.). Inoculation theory or pre-bunking, where communities are equipped with the health literacy needed to evaluate (mis)information before it takes hold (Cook et al.; Jolley and Douglas), can potentially address vaccine hesitancy by empowering communities with knowledge. Many Indigenous communities and organisations are already taking pre-bunking approaches. Organisations such Why Warriors, for example, have remained dedicated to providing accessible information that empowers Aboriginal communities to make informed decisions. Why Warriors, based in Yolngu Country in the Northern Territory has procured a range of resources including podcasts, radio outputs, videos, and in-person sessions held in Yolngu Matha language (Why Warriors). The organisation has observed that there is a great desire for in-depth scientific knowledge pertaining to the virus within Aboriginal communities; however, this is not always accessible due to language and cross-cultural barriers. The resources Why Warriors produce are based on an informed cross-cultural methodology that seeks to understand and respond to communities’ concerns and the drivers behind vaccine hesitancy. The information provided is based on medical and Indigenous knowledge, and is a direct response to the questions, information gaps, and contradictions prevalent in community. Why Warriors is just one example of culturally appropriate approaches to pre-bunking that “is not just about getting vaccinated but having a well-rounded understanding of the whole subject in order to deal with new developments and health issues in the future” (Trudgen et al. 3). The organisation with community organisations and frontline workers has successfully boosted vaccination rates, with estimates indicating that due to their community engagement on Elcho Island, and a presence during the Galiwin'ku Festival, vaccination rates increased from 30 inoculations to 80 per day (Trudgen et al.). Conclusion The word “conspire” derives from Latin, meaning to “breathe together” (Jane and Fleming). Co-designed Indigenous-led partnerships between governments (policymakers) and Indigenous communities are critical in ensuring that community leaders, organisations, and frontline workers are adequately resourced and financed so that health literacy can be improved as a protective strategy. For many Indigenous peoples, mistrust in government-led health interventions such as the COVID-19 vaccination rollout is a by-product of settler-colonialism informed by a history of state-sanctioned violence, invasion (of Country and body), and punitive measures of control. For some Indigenous people, conspiracies may provide an outlet through which to voice outrage at white systems of governance that are inherently violent and oppressive. While mistrust does not necessarily equate to a proclivity towards conspiracy theories, greater accessibility to misinformation online has provided fertile ground for an infodemic of manipulated and distorted facts, circulated for personal and/or ideological gain (Alam and Chu). The stakeholders who contributed to UQ’s study on COVID-19 responses in urban Indigenous communities expressed their grave concerns over the impact of spreading misinformation. Such mistruths have the potential of further infiltrating Aboriginal and Torres Strait Islander communities, exacerbating pre-existing anxieties, breaking down trust and relationships, and having a ripple effect that places an already vulnerable population at further risk of succumbing to COVID-19. Throughout this article we have discussed the spread of misinformation primarily through conspiracy theories with religious connotations and that liken vaccination to the biblical reference of the “mark of the Beast”. It is important to note, however, that such claims represent an extremist view and have been refuted by religious leaders such as Aboriginal pastor Geoffrey Stoke and, at the highest level, Pope Francis. Within communities where distrust of government is ripe, and fears and lived experiences of disposition ongoing, rumours and misinformation can quickly spread via social networks. Whilst more needs to be done to regulate the spread of misinformation on social and online media, responses to information gaps and trust in health directives must be informed by Indigenous peoples, including the messaging. The stakeholders who took part in UQ’s study identified several touchpoints where interventions could help counter the spread of misinformation and the mistruths that compromise preventative behaviours. Some of these include: Substantiating medical messaging with the voices of Elders, leaders, and trusted community members. Increasing the Indigenous workforce to continue to provide trusted services, while also offsetting burnout. Provide greater resourcing and financing to existing services who are carrying the burden of countering misinformation, often from sources external to the community. Recognise that services and organisations may help engage Indigenous communities and provide access to verified information. Address the systemic and underlying social and health “gaps” that inform Indigenous peoples’ vulnerabilities and contribute to a culture of mistrust in non-Indigenous authorities. Create and/or enforce the legal and political mechanisms that will ensure Indigenous representation across all levels of governments and provide a voice that may oversee the implementation of co-designed strategies. The burden carried as a result of spreading conspiracy theories can be alleviated by empowering Indigenous communities via decision-making and governance processes, creating structural and systemic change, closing pre-existing health gaps, improving health literacy, and increasing Indigenous representation in the workforce and across all levels of government, along with resourcing. Only when health systems “breathe together” with Indigenous peoples may the burden of the so-called Beast be overcome, and Indigenous and non-Indigenous peoples can collectively conspire towards equitable health outcomes. References Aboriginal Medical Services Alliance Northern Territory. "Blackfishing Used to Spread Anti-Vax Message: From the Weekend Australian." Facebook 29 Jan. 2022. 30 Jan. 2022 . Alam, Noore, and Cordia Chu. “Covid-19 Pandemic: Tackling ‘Infodemics’ through an Integrated One Health–Social Science Approach”. Proceedings of The Royal Society of Queensland 128 (2020). Allam, Lorena. "‘Tinfoil Hat Wearing Tossers’: Nt Chief Minister and Aboriginal Elders Hit Back at Covid ‘False Information’." The Guardian, 25 Nov. 2021. 3 Dec. 2021 . Anderson, Warwick. The Cultivation of Whiteness: Science, Health, and Racial Destiny in Australia. Duke University Press, 2006. Andrews, Robert. "Using Conspiracy Theories to Teach Source Analysis." Teaching History 48.4 (2014): 64-65. . Bain, Lucy. "‘Myths’ Harmed Indigenous Vaccine Rate, Says Mdas." Sunraysia Daily, 6 Sep. 2021. 17 Sep. 2021 . Bargallie, Debbie. Unmasking the Racial Contract: Indigenous Voices on Racism in the Australian Public Service. Aboriginal Studies Press, 2020. Barkun, Michael. A Culture of Conspiracy. Berkeley: University of California Press, 2013. Bohlinger, Tavis. "The Covid Vaccine Has 666 Written All over It… and Why That Doesn’t Matter According to Revelation." theLAB 18 May 2020. 7 Sep. 2021 >https://academic.logos.com/the-covid-vaccine-has-666-written-all-over-it-and-why-that-doesnt-matter-according-to-revelation/>. Bottoms, Timothy, and Raymond Evans. “European Invasion of the Future Central Queensland.” In Conspiracy of Silence: Queensland's Frontier Killing-Times. Ed. T. Bottoms. Crows Nest, NSW: Allen & Unwin, 2013. 46–59. Bruns, Axel, Stephen Harrington, and Edward Hurcombe. "'Corona? 5G? Or Both?’: The Dynamics of COVID-19/5G Conspiracy Theories on Facebook." Media International Australia 177 (2020): 12-29. . Butts, Amber. "Even When Black Conspiracy Theories Are Misguided, They Are Not Nonsensical." Racebaitr 1 Oct. 2019. 18 Sep. 2021 . Byrne, Conor, Jack Hislop, and Adam Steer. "Doctor Warns Anti-Vax Rumours, 'All Sorts of Really Weird, Irrational Logic', Rife in Remote Communities." ABC News 30 Sep. 2021. 1 Oct. 2021 . Carlson, Bronwyn, and Ryan Frazer. "Social Media Mob: Being Indigenous Online." Sydney: Macquarie University, 2018. Carlson, Bronwyn, Ryan Frazer, and Terri Farrelly. “‘That Makes All the Difference’: Aboriginal and Torres Strait Islander Health-Seeking on Social Media.” Health Promotion Journal of Australia 32.3 (2021): 523-531 . Coade, Melissa. “Minister Tries to Map Path to Boost Vaccine Rates among Indigenous Australians.” The Mandarin 7 Sep. 2021. 2 Oct. 2021 . Compton, Josh, Sander van der Linden, John Cook, and Melisa Basol. "Inoculation Theory in the Post‐Truth Era: Extant Findings and New Frontiers for Contested Science, Misinformation, and Conspiracy Theories." Social and Personality Psychology Compass 15.6 (2021): e12602. . Cook, John, Stephan Lewandowsky, and Ullrich KH Ecker. "Neutralizing Misinformation through Inoculation: Exposing Misleading Argumentation Techniques Reduces Their Influence." PloS one 12.5 (2017): e0175799. . Coughlan, Matt. “Indigenous Leaders in Talks over Jab Lies.” The Canberra Times 6 Sep. 2021. 10 Sep. 2021 . Cromb, Nat. “COVOD-19 and Custody – Calls for Release.” IndigenousX 25 Mar. 2020. 17 July 2021 . Danchin, Margie, Ruby Biezen, Jo-Anne Manski-Nankervis, Jessica Kaufman, and Julie Leask. "Preparing the Public for Covid-19 Vaccines: How Can General Practitioners Build Vaccine Confidence and Optimise Uptake for Themselves and Their Patients?" Australian Journal of General Practice 49.10 (2020): 625-29. . Day, Madi, and Bronwyn Carlson. "White Supremacist and Far Ri